2001
DOI: 10.1111/j.1574-695x.2001.tb01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokine production by synoviocytes following exposure to protein I/II, a modulin from oral streptococci

Abstract: We have tested the ability of protein I/II, an adhesin from oral streptococci, to stimulate the production of pro-inflammatory cytokines by synovial cells isolated from both rheumatoid arthritis and control patients. Protein I/II triggers synovial fluid cells to produce interleukin (IL)-6 and IL-8 while secretion of tumor necrosis factor-alpha (TNF-alpha) was less enhanced. Using fibroblast-like synoviocytes, we found that protein I/II also exerts an immunomodulatory effect (IL-6 and IL-8 release) on these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Protein I/II-induced expression of IL-6 and IL-8 mRNA from human FLSs In a previous work, we demonstrated that protein I/II induces the release of IL-6 and IL-8 from FLSs isolated from RA patients (Gourieux et al, 2000). To assess the specific induction of these cytokines by protein I/II in stimulated human FLSs, reverse transcription±polymerase chain reaction (RT±PCR) was performed with RNA isolated from human FLSs activated with 125 pM protein I/II for various times.…”
Section: Resultsmentioning
confidence: 91%
“…Protein I/II-induced expression of IL-6 and IL-8 mRNA from human FLSs In a previous work, we demonstrated that protein I/II induces the release of IL-6 and IL-8 from FLSs isolated from RA patients (Gourieux et al, 2000). To assess the specific induction of these cytokines by protein I/II in stimulated human FLSs, reverse transcription±polymerase chain reaction (RT±PCR) was performed with RNA isolated from human FLSs activated with 125 pM protein I/II for various times.…”
Section: Resultsmentioning
confidence: 91%
“…lipopolysaccharide, polyosides, lipoteichoic acids, and proteins), after binding to their cognate receptors on different eukaryotic cells, is controlled by the MAPKs pathway and that this synthesis may play an important role in innate immunity as well as in various inflammatory disorders (9,10). Using protein I/II, a PAMP from oral streptococci, we reported previously that interaction of this cell wall component with fibroblast-like synoviocytes (FLSs), cells that are critically involved in rheumatoid arthritis-associated joint inflammation, triggers the production and release of inflammatory mediators such as IL-6 and IL-8 (11,12). This cytokine synthesis involves ERK 1/2 and JNKs as well as AP-1-binding activity and nuclear translocation of NF-B (13).…”
mentioning
confidence: 99%
“…For example, invasion of dentinal tubules by oral streptococci is associated with collagen recognition mediated by antigen I/II polypeptide, leading to dissemination of the bacteria and expression of its cariogenic phenotype [17]. In addition, the immunomodulatory effects of the antigen on human cells may be associated with inflammatory disorders [13,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Much interest has been focused on the antigen I/II family polypeptides expressed at the cell surface of oral streptococci [9]. Antigens I/II are multifunctional adhesins that exert diverse binding activities, i.e., with salivary glycoproteins [10], host cell receptors [11][12][13][14] and soluble extracellular matrix glycoprotein [15,16]. For example, invasion of dentinal tubules by oral streptococci is associated with collagen recognition mediated by antigen I/II polypeptide, leading to dissemination of the bacteria and expression of its cariogenic phenotype [17].…”
Section: Introductionmentioning
confidence: 99%